Transforming Learning Management with Class of Champions: Exploring its Effect on Student Cooperation - Firda Ambar Agustin; Rozy, Fakhrur (Journal of Educational Management Research, 2025)
This study examines the impact of the Class of Champions game on student collaboration during Civics Education lessons. Collaboration is key to effective learning, and this research highlights its importance in achieving educational success. Using a quantitative descriptive method with 25 students, the study utilised a collaboration assessment sheet with eight indicators, which was tested for validity and reliability on 28 students. Results showed valid indicators with correlation coefficients ranging from 0.554 to 0.908 and a Cronbach's Alpha of 0.893, indicating high reliability. The analysis revealed that student collaboration was rated as "good" to "very good," with an average score of 27.88. The study concludes that the game effectively fostered student interaction and teamwork. Additionally, it emphasises the role of educational management in integrating game-based learning to enhance collaboration. Educational managers can utilise these tools to create an engaging classroom environment, improve social learning skills, and foster innovative teaching approaches. This research demonstrates the potential of game-based learning to enhance collaboration and engagement in the classroom.